A novel function for CUGBP2 in controlling the pro-inflammatory stimulus in H9c2 cells: Subcellular trafficking of messenger molecules - Moraes, Karen C. M. [UNESP]; Monteiro, Cíntia Júnia; Pacheco-Soares, Cristina (Wiley, 2013)
Accumulating evidence demonstrates that chronic inflammation plays an important role in heart hypertrophy and cardiac diseases. However, the fine-tuning of cellular and molecular mechanisms that connect inflammatory process and cardiac diseases is still under investigation. Many reports have demonstrated that the overexpression of the cyclooxygenase-2 (COX-2), a key enzyme in the conversion of arachidonic acid to prostaglandins and other prostanoids, is correlated with inflammatory processes. Increased level of prostaglandin E2 was also found in animal model of left ventricle of hypertrophy. Based on previous observations that demonstrated a regulatory loop between COX-2 and the RNA-binding protein CUGBP2, we studied cellular and molecular mechanisms of a pro-inflammatory stimulus in a cardiac cell to verify if the above two molecules could be correlated with the inflammatory process in the heart. A cellular model of investigation was established and H9c2 was used.We also demonstrated a regulatory connection between COX-2 and CUGBP2 in the cardiac cells. Based on a set of different assays including gene silencing and fluorescence microscopy, we describe a novel function for the RNA-binding protein CUGBP2 in controlling the pro-inflammatory stimulus: subcellular trafficking of messenger molecules to specific cytoplasmic stress granules to maintain homeostasis. © 2013 International Federation for Cell Biology.
Keywords: Cellular homeostasis; CUGBP2; H9c2 cells; Pro-inflammatory stimulus; Stress granules; Subcellular translocation